2015
DOI: 10.1016/j.biocon.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protected area management effectiveness over time: A global analysis

Abstract: 32 Protected Area coverage has reached over 15% of the global land area. However, the quality of 33 management of the vast majority of reserves remains unknown, and many are suspected to be 34 'paper parks'. Moreover, the degree to which management can be enhanced through targeted 35 conservation projects remains broadly speculative. Proven links between improved reserve 36 management and the delivery of conservation outcomes are even more elusive. In this paper we 37 present results on how management effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 37 publications
2
132
0
14
Order By: Relevance
“…In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants. Concerns also exist on the role of protected areas, in general, in providing effective biodiversity conservation (Geldmann et al, 2015;Le Saout et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants. Concerns also exist on the role of protected areas, in general, in providing effective biodiversity conservation (Geldmann et al, 2015;Le Saout et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Parties were invited to implement management effectiveness evaluations in at least 60 per cent of their total protected areas (CBD, 2010b). As of January 2015, only 21.4 per cent of CBD Parties, excluding overseas territories, had met this target (Coad et al, 2015). However, the Global Database for Protected Area Management Effectiveness (GD-PAME) contains information for only a small portion of the sites listed in the WDPA (UNEP-WCMC, 2017b).…”
Section: Effective and Equitable Managementmentioning
confidence: 99%
“…This is positive in the sense that it illustrates how the implementation of adaptive processes may be improving protected area management, though the relation to biodiversity impacts is indirect. More work is needed to comprehend the connections between management effectiveness and biodiversity outcomes (Coad et al, 2015;.…”
Section: Effective and Equitable Managementmentioning
confidence: 99%
“…Protected areas are one of the most effective mechanisms for achieving conservation and afford a high level of defence against biodiversity loss and environmental degradation (Geldmann et al 2015). They require constant management and monitoring to be effective Watson et al 2014;Coad et al 2015;Pressey et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They require constant management and monitoring to be effective Watson et al 2014;Coad et al 2015;Pressey et al 2015). Effective management of protected areas requires sound practices and an appropriate level of management and resources which may frequently be limited (Shoo et al 2014).…”
Section: Introductionmentioning
confidence: 99%